Regulation of P-glycoprotein 1 and 2 gene expression and protein activity in two MCF-7/Dox cell line subclones. - Davies, R. (Nature Publishing Group, 1996)
The MCF-7 doxorubicin-resistant cell line MCF-7/Dox has been used extensively for studies of the multidrug resistance phenomenon. Using fluorescence-activated cell sorting (FACS), these cells were separated into two populations on the basis of rhodamine 123 (R123) accumulation. We designated these as low P-glycoprotein (LP-gp) and high P-gp (HP-gp) cells on the basis of their P-gp content. Using the reverse transcriptase polymerase chain reaction technique controlled by homologous internal standards, we analysed levels of MDR1 and MDR2 mRNA in each cell type. LP-gp and HP-gp cells had MDR1 mRNA levels of 2.17 +/- 0.17 and 6.65 +/- 2.29 amol ng-1 total RNA respectively, compared with 0.00088 +/- 0.00005 amol ng-1 in wild-type MCF-7 cells (MCF-7/WT). MCF-7/WT cells additionally contained 0.023 +/- 0.016 amol ng-1 of MDR2 mRNA, which was unchanged in LP-gp cells, but lower than in HP-gp cells, which contained 0.42 +/- 0.08 amol ng-1. Both LP-gp and HP-gp cells contained increased copies of the MDR1 gene. However, the degree of gene amplification did not correlate with the changes in MDR1 mRNA levels, indicating further regulatory levels of gene expression. The level of P-gp detected by MRK 16 correlated with R123 accumulation. HP-gp cells expressed a 10-fold higher level of P-gp1 than LP-gp cells. However, there was only a 3-fold increase in MDR1 mRNA level in HP-gp cells compared with LP-gp cells. These data suggest that some regulation of P-gp1 expression also occurred at the post-translational level. Phosphorylation of P-gp by protein kinase C (PKC)-alpha is necessary for its activity. Our analysis of PKC-alpha, 0 and epsilon isozyme levels, and subcellular distribution, shows a co-regulation of expression with P-gp, suggesting a necessary role for PKC in P-gp regulation. IMAGES: